PrototypeSistem Informasi Akademik Berbasis Mobile Applicationdengan TeknologiJava 2 Micro Edition(J2ME) - Siregar, Syahriani F (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2013)
Handphone is mobile device and as amedia that is able to do various communicationsdata which users are able to acces internet anytimeand anywhere. Based on this condition, comes thewill to develop a spesific application in mobilesdevice which needs a lot of mobiling. Collagestudents has needs for academic informations and itis very important to them. Application that canmake students access their academic informationthrough handphone has to be developed. Therefore,a technology that can make collage student accesstheir academic informations through handphone ishighly needed and Java 2 Micro Edition (J2ME) cando it. This application can hopefully help and makecollage students access their academic informationseasier through their handphones with GeneralPacket Radio Services (GPRS) as it’s network. Theapplications is made based on mobile fromhandphone that supports Java. Client-serverapplication which is called midlet, is installed intothe handphone. To be connected to the server, thisapplication is using GPRS as a connection. The testresult shows that this application can accessacademic information online with GPRS network, socollage students can use this application anywhereand everywhere as far as the operator mobile can bereach.